Community Empowerment about Components for Destination Development in Tipang Tourism Village, Baktiraja District, Humbang Hasundutan Regency - Sibarani, Robert; Davin Gumuruh Marpaung; Christian Basardo Simanjuntak; Bintang Terang Putra Utara Purba; Muhammad Mirza Ramadhan; Timothy Novritrianta Ibrena; Cosmas Mitchel Pandapotan Siallangan; Prima Nopraka Tarigan; Elizabeth Bintang Paulaean; Ariani Safitri; Atikah Ab Zubaidi; Florence Hermin Puspita Sari Waruwu; Riska Berlian; Kristina Sihotang; Amanda Dwi Cahya; Caroline Feryna Br Manik; Hanifah Nasution; Lisa Meylisa Damanik (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2023)
The Community Service Program (KKN) is a form of education in the form of community service. In this service students are given learning experience to live in the midst of a community outside the campus and directly identify and deal with development problems they face. Community Empowerment Learning Thematic Real Work Lecture Program (KKNT-PPM), which is a learning process basically focuses on problems that exist in society. Tipang Village is one of the villages in Baktiraja District, Humbang Hasundutan Regency, North Sumatra Province. This village is one of the villages included in the "50 Indonesian Tourism Award Villages" in 2021. Tipang is one of the villages that has high tourism potential, both in terms of Natural Resources (SDA) and Human Resources (HR) so that it delivers This village is one of the tourist villages. Students who are placed in Tipang Village, Baktiraja District, Humbang Hasundutan Regency have the aim of developing programs for accessibility, ansilari (community empowerment), amenities, cultural attractions, sciences and technology (Technology), and agriculture. This aims to support and develop human resources and tourism aspects in Tipang Village, Baktiraja District, Humbang Hasundutan Regency.